Microwave synthesis of phosphorus-doped graphitic carbon nitride nanosheets with enhanced electrochemiluminescence signals - Zou, Jingye; Yu, Yongzhi; Qiao, Kun; Wu, Shan; Yan, Wenjun; Cheng, Si; Jiang, Nan; Wang, Jigang (Journal of materials science, 2020)
Efficient and low-cost electrode materials for the electrochemiluminescence (ECL) reaction are highly desired for the future detection technology. Herein, we report an efficient bottom-up pathway to synthesize phosphorus-doped graphitic carbon nitride nanosheets (PCNNs) by ultra-rapid microwave irradiation. When the melamine precursor is modified with a 5 wt% diammonium hydrogen phosphate, the as-synthesized PCNNs display a very thin thickness (about 2 nm), good dispersibility in water (still stable after 2 weeks), low electron-transfer resistance (7499 Ω) and suitable band gap (2.7 eV). More importantly, the ECL intensity of the optimal PCNNs at low potential (− 1.2 to 0 V) is 26.7 times stronger than that of pure graphitic carbon nitride. The key to the excellent ECL property primarily lies in the more satisfactory sheet-like structure, faster electron transfer and better water affinity.